Dental self-perception and clinical dental description of participants in the Open University programme for elderly people - Geovane Evangelista MOREIRA; Laura Ferreira SILVA; Marina Reis OLIVEIRA; Larissa Soares Reis MAIA; Leandro Araújo FERNANDES; Daniela Coelho LIMA (Faculdade São Leopoldo Mandic, 2018)
Objective: This study verified both the self-perception and oral characteristics of a group of elderly participants of the Open University for the Elderly (UNATI). Methods: The sample consisted of a cross-sectional epidemiological study with elderly subjects (50 years of age or older), who attended the UNATI-UNIFAL/MG program. Data collection was carried out using a semi-structured questionnaire consisting of open- and closed-ended questions regarding oral health, its interference with self-esteem and nutrition, among other features. In addition, an application form based on the proposals by the Oral Health Survey 2010, was used. Univariate and multivariate descriptive analyses were performed. Results: The study sample consisted of 106 subjects (mean age of 62.4 years), of whom 59.4% had attended a dental appointment in the last year for routine and/or aesthetic examinations (38.7%). The clinical conditions showed that only 19.8% of the subjects were completely edentulous, an average DMFT of 26.1, and 37.7% used some kind of complete upper dentures, complete lower dentures, or both. Regarding self-perception of oral conditions, 34.9% considered it a regular perception, however in the applied statistics the presence of pain demonstrated a worse perception which was not correlated with teeth loss, presence of dentures and/or restored teeth. Conclusion: The self-perception of oral conditions is regular and the clinical and odontological characteristics evaluated revealed partial edentulous subjects with high DMFT. By evaluating the odontological aspects, it was observed that the majority of the subjects did not have difficulties to look for a dentist, they attended dental appointments in the last year and the preventive treatment had been the most required.